Exploration of Small Non-Coding RNAs as Molecular Markers of Ram Sperm Fertility - Bodu, Mustafa; Hitit, Mustafa; Donmez, Huseyin; Kaya, Abdullah; Ugur, Muhammet Rasit; Memili, Erdoğan (MDPI AG, 2025)
The identification of molecular markers for fertility is critical for the sustainability of livestock production. We profiled small non-coding RNAs (sncRNAs) in sperm from rams with high fertility (HF) and low fertility (LF) phenotypes to uncover their roles in ram sperm fertility. Rams were categorized into high-fertility (HF, n = 31; 94.5 ± 2.8%) and low-fertility (LF, n = 25; 83.1 ± 5.73%) phenotypes based on pregnancy rates (average 89.4 ± 7.2%). From these, sperm samples of HF (n = 4; pregnancy rate 99.2 ± 1.6%) and LF (n = 4; pregnancy rate 73.6 ± 4.4%) rams underwent sncRNA sequencing. Small RNA sequencing produced 14,962,876 reads in LF rams and 17,401,094 reads in HF rams, showing distinct sncRNA biotypes, including miRNAs, tRNAs, snoRNAs, snRNAs, and rRNAs. Among these, miRNAs comprised 7.12% of reads in LF rams and 3.78% in HF rams, while rRNAs and repeats formed significant proportions in both groups. A total of 1673 known and 627 novel miRNAs were identified, with 227 differentially expressed miRNAs between the HF and LF groups. We showed that key miRNAs, such as oar-miR-200b and oar-miR-370-3p, were upregulated in HF sperm, while downregulated miRNAs in LF, such as oar-miR-26b and oar-let-7d, were associated with impaired sperm function and DNA fragmentation. A functional enrichment analysis of miRNA target genes highlighted pathways related to ribonucleoprotein complex biogenesis, RNA processing, and gene expression regulation. These findings establish the critical role of sperm sncRNAs as regulators of fertility and potential biomarkers in breeding soundness tests for the precision farming of livestock for global food security.
Keywords: Male; MicroRNAs; Fertility; Sheep; Pregnancy; Gene Expression Profiling; Animals; RNA, Small Untranslated; Female; Spermatozoa; Article; Biomarkers